Penerapan Analisis Portofolio Saham dalam Rangka Optimalisasi Return dan Minimlisasi Risiko pada Perusahaan Blue Chips - Helda Puji Sofiana; Heri Widodo (Universitas Negeri Surabaya, 2018)
A financial accounting established by a company is the financial accounting that is going on the basis of previous events with the stable prices assumption. The truth of the excess of costs such as historical cost on the real transaction can be tested and proved by objective evidences, so that the financial accounting formed on the basis of historical cost is believable to be audited well. In fact, the change of price always happens and moreover it is inclined to rise. In other word, there will be inflation. Related with the fact, the historical cost concept applied in the financial accounting is judged to give less information to make a decision. The objectives of the study are to describe the inflation of accounting treatment by using General Price Level Accounting (GPLA) and Current Cost Accounting (CCA) methods as an additional report rather than the conventional financial accounting as the main report, and to know the additional financial accounting. The methods used are General Price Level Accounting (GPLA) and Current Cost Accounting (CCA) methods. In conclusion, the inflation accounting as an additional information is very useful for the financial accounting users to make economics decision. Furthermore, it also benefits in order to maintain the capital as the first period so that the continuity of companys activity runs well